2011
DOI: 10.1364/ol.36.002524
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental structure of Fresnel diffraction: natural sampling grid and the fractional Fourier transform

Abstract: Fresnel integrals corresponding to different distances can be interpreted as scaled fractional Fourier transformations observed on spherical reference surfaces. We show that by judiciously choosing sample points on these curved reference surfaces, it is possible to represent the diffracted signals in a nonredundant manner. The change in sample spacing with distance reflects the structure of Fresnel diffraction. This sampling grid also provides a simple and robust basis for accurate and efficient computation, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 19 publications
2
18
0
Order By: Relevance
“…The derivation of these results are similar to those in [37] and are thus not repeated. On the output plane, the space-bandwidth product is σ ″ = Δ ″Δ ″ N x x .…”
Section: Transverse Sampling Spacingmentioning
confidence: 66%
See 1 more Smart Citation
“…The derivation of these results are similar to those in [37] and are thus not repeated. On the output plane, the space-bandwidth product is σ ″ = Δ ″Δ ″ N x x .…”
Section: Transverse Sampling Spacingmentioning
confidence: 66%
“…The parameters Δx and σ Δ x defines s and δa, which mirrors the information content of the set of signals. The special value σ = Δ Δ s x/ x matches the structure of the grid to the natural propensity of the signal to diffract, as determined by its space and frequency extent [37]. Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier, we showed that by appropriately choosing sample points on these reference surfaces, it is possible to represent the diffracted signals in a nonredundant manner [1]. Here we show that these reference surfaces should be spaced equally with respect to the fractional Fourier transform order, rather than with respect to the distance of propagation.…”
mentioning
confidence: 74%
“…In [1], we showed that if we choose s Δx∕Δσ x p , then the spatial and spatial frequency extents of the diffracted signal on the spherical reference surface are Δx 0 MΔx;…”
mentioning
confidence: 99%
See 1 more Smart Citation